PENGEMBANGAN PRODUK SOSIS FUNGSIONAL BERBAHAN DASAR IKAN TENGGIRI (Scomberomorus sp.) DAN TEPUNG DAUN KELOR (Moringa oleifera L) - Nurlaila Nurlaila; Andi Sukainah; Amiruddin Amiruddin (Universitas Negeri Makassar, 2016)
The purpose of this research is to know the nutrition of the fish sausage and the acceptation of the panellist of the functional fish sausage. This research was done by two steps which the first step is hedonic test and the second step is chemistry analysis. The data analysis used Completely Randomized Design and analysis of variances (ANOVA) which was tested with least significant different test (BNT) in 5% extent. The Result of research shows that the best of water levels treatment of A3B1 (600gr of fish meat + 5gr of moringa flour) is 62.77%, protein levels of A3B1 (600gr fish meat + 5gr moringa flour) is 27%, fat levels A1B0 (200gr of fish meat + without moringa flour) is 2.22%